2014
DOI: 10.1007/s10886-014-0388-2
|View full text |Cite
|
Sign up to set email alerts
|

Glycerophospholipid Analysis of Eastern Red Bat (Lasiurus Borealis) Hair by Electrospray Ionization Tandem Mass Spectrometry

Abstract: Pilosebaceous units found in the mammalian integument are composed of a hair follicle, the proximal portion of the hair shaft, a sebaceous gland, and the erector pili muscle. Pilosebaceous units release protective oils, or sebum, by holocrine secretion onto skin and hair through rupturing of sebocytes. Sebum is largely composed of polar and neutral lipids including glycerolipids, free fatty acids, sterols, wax esters, sterol esters, and squalene. In addition to these lipid classes, there is a small proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
2
4
0
Order By: Relevance
“…SM FAs from R. aegyptiacus brain and spinal cord (primarily 18:0, 24:0/24:1, and >24 C lengths; van der Westhuyzen and Cantrill 1983) are characterized by longer chain lengths compared to M. lucifugus wing tissue SM FAs we describe (predominantly 16:0 with lower amounts of 18:0, 22:1, 22:0, 24:1, and 24:0). The GP fraction in our study was similar to that observed for L. borealis hair sebaceous lipid (Pannkuk et al 2014b), but there were minor differences. While PC (~70%) and PI (~15%) were dominant GP classes in L. borealis hair (Pannkuk et al 2014b), here we found that PC (~30%) and PS (~21%) were dominant in wing tissue.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…SM FAs from R. aegyptiacus brain and spinal cord (primarily 18:0, 24:0/24:1, and >24 C lengths; van der Westhuyzen and Cantrill 1983) are characterized by longer chain lengths compared to M. lucifugus wing tissue SM FAs we describe (predominantly 16:0 with lower amounts of 18:0, 22:1, 22:0, 24:1, and 24:0). The GP fraction in our study was similar to that observed for L. borealis hair sebaceous lipid (Pannkuk et al 2014b), but there were minor differences. While PC (~70%) and PI (~15%) were dominant GP classes in L. borealis hair (Pannkuk et al 2014b), here we found that PC (~30%) and PS (~21%) were dominant in wing tissue.…”
Section: Discussionsupporting
confidence: 87%
“…The GP fraction in our study was similar to that observed for L. borealis hair sebaceous lipid (Pannkuk et al 2014b), but there were minor differences. While PC (~70%) and PI (~15%) were dominant GP classes in L. borealis hair (Pannkuk et al 2014b), here we found that PC (~30%) and PS (~21%) were dominant in wing tissue. LPCs were similar between L. borealis hair and M. lucifugus wing tissue with 16:0, 18:0, and 18:1 dominant FAs.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations